The complete adult psychotherapy treatment planner - Jongsma, E. (PracticePlanners, 2021)
Revised and updated, the sixth edition of The Complete Adult Psychotherapy Treatment Planner offers clinicians a timesaving, evidence-based guide that helps to clarify, simplify and accelerate the treatment planning process so they can spend less time on paperwork and more time with clients. The authors provide all the elements necessary to quickly and easily develop formal, customizable treatment plans that satisfy the demands of HMOs, managed-care companies, third-party payers and state and federal agencies. This revised edition includes new client Short-Term Objectives and clinician Therapeutic Interventions that are grounded in evidence-based treatment wherever research data provides support to an intervention approach. If no research support is available a best practice standard is provided. This new edition also offers two new presenting problem chapters (Loneliness and Opioid Use Disorder) and the authors have updated the content throughout the book to improve clarity, conciseness and accuracy. This important book: Offers a completely updated resource that helps clinicians quickly develop effective, evidence-based treatment plans Includes an easy-to-use format locating treatment plan components by Presenting Problem or DSM-5 diagnosis Contains over 3,000 prewritten treatment Symptoms, Goals, Objectives and Interventions to select from Presents evidence-based treatment plan components for 45 behaviorally defined Presenting Problems Suggests homework exercises specifically created for each Presenting Problem Written for psychologists, therapists, counselors, social workers, addiction counselors, psychiatrists, and other mental health professionals, The Complete Adult Psychotherapy Treatment Planner, Sixth Edition has been updated to contain the most recent interventions that are evidence-based.